Adamantane-Substituted Purine Nucleosides: Synthesis, Host-Guest Complexes with β-Cyclodextrin and Biological Activity - Rudolfová, Jana; Kryštof, Vladimír; Nečas, Marek; Vícha, Robert; Rouchal, Michal (International journal of molecular sciences, 2022)
Purine nucleosides represent an interesting group of nitrogen heterocycles, showing a wide range of biological effects. In this study, we designed and synthesized a series of 6,9-disubstituted and 2,6,9-trisubstituted purine ribonucleosides via consecutive nucleophilic aromatic substitution, glycosylation, and deprotection of the ribofuranose unit. We prepared eight new purine nucleosides bearing unique adamantylated aromatic amines at position 6. Additionally, the ability of the synthesized purine nucleosides to form stable host-guest complexes with β-cyclodextrin (β-CD) was confirmed using nuclear magnetic resonance (NMR) and mass spectrometry (ESI-MS) experiments. The in vitro antiproliferative activity of purine nucleosides and their equimolar mixtures with β-CD was tested against two types of human tumor cell line. Six adamantane-based purine nucleosides showed an antiproliferative activity in the micromolar range. Moreover, their effect was only slightly suppressed by the presence of β-CD, which was probably due to the competitive binding of the corresponding purine nucleoside inside the β-CD cavity.
Keywords: glycosylation; Adamantane; beta-cyklodextriny; Nucleosides; adamantan; purine; antiproliferative activity; lidé; Purine Nucleosides; beta-Cyclodextrins; nucleoside; Cell Line, Tumor; β-cyclodextrin; adamantane; nádorové buněčné linie; nukleosidy; purinové nukleosidy; Humans